Transforming our nuclear future with ridiculous ideas. (1st November 2020) - Belcher, Emma
ABSTRACT: Success in achieving the goals of reducing and eventually eliminating nuclear weapons will rely on several interrelated factors: A revitalized nuclear policy field that recognizes the power that comes from greater diversity in all its forms, new partners willing to share their knowledge and expertise, and bold new ideas – some of which, by design, will appear ridiculous at first.